Effects of acupuncture medication combined on facial function and mimetic muscle strength and motor conduction in patients with peripheral facial palsy - Bu, Xiuhuan; Wang, Lei; Wang, Tian (Journal of acupuncture and tuina science, 2024)
Objective To observe the improvement of facial weakness in patients with peripheral facial palsy treated with needling the muscle regions of meridians plus Da Qin Jiao Tang [decoction of Qin Jiao ( Radix Gentianae Macrophyllae )], and the effects on facial paralysis injury function and mimetic muscle atrophy and motor conduction. Methods A total of 120 patients with peripheral facial palsy were randomized into a Chinese medication group and an acupuncture medication combined group by the random number table method, with 60 cases in each group. The Chinese medication group was treated with Da Qin Jiao Tang, and the acupuncture medication combined group was treated with needling the muscle regions of meridians based on oral Da Qin Jiao Tang. After treatment, the clinical efficacy was compared between the two groups. The changes in the facial symptom score, facial muscle thickness, facial muscle strength, facial nerve function, and facial disability index were observed. Results The total effective rate in the acupuncture medication combined group was 98.3%, which was higher than 85.0% in the Chinese medication group ( P <0.05). Each facial symptom score in the acupuncture medication combined group was lower than that in the Chinese medication group ( P <0.05). The muscle thickness of the depressor anguli oris, frontalis, and depressor labii inferioris in the acupuncture medication combined group was thicker than that in the Chinese medication group ( P <0.05). The scores of physical function and social/behavioral function in the acupuncture medication combined group were lower than those in the Chinese medication group ( P <0.05), while the scores of manual muscle test (MMT) and Sunnybrook facial nerve were higher than those in the Chinese medication group ( P <0.05). The facial nerve motor latency of the upper lip quadrate muscle, frontalis, and orbicularis oculi in the acupuncture medication combined group was lower than that in the Chinese medication group ( P <0.05), while the M-wave amplitude was higher than that in the Chinese medication group ( P <0.05). Conclusion Needling the muscle regions of meridians plus Da Qin Jiao Tang can improve facial muscle strength, mimetic muscle atrophy, facial paralysis function injury, and facial nerve motor conduction in the treatment of peripheral facial palsy and enhance clinical efficacy.